Embezzlement in Corruption Crimes: A Case Study of Government Procurement of Goods and Services - Firdaus, Mohammad; Darmawan, Didit; Saputra, Rio (Metromedia, 2022)
Embezzlement in public procurement corruption is a significant problem in Indonesia. This study aims to analyze the frequent modus operandi of embezzlement in this sector and evaluate its law enforcement efforts. The findings show that budget inflation, manipulation of tender documents, and fictitious procurement are common modes. The main enabling factors for embezzlement are weaknesses in the oversight system and lack of transparency in the procurement process. Law enforcement efforts still face major challenges, including a lack of coordination between government agencies and law enforcement. The study suggests bureaucratic reform, strengthening regulations, and implementing technology as important steps to improve integrity in public procurement.